Heparin-binding protein as a biomarker of gastrointestinal dysfunction in critically ill patients: a retrospective cross-sectional study in China. Issue 7 (5th July 2020) - Sun, Jia-Kui; Shen, Xiao; Sun, Xin-Pei; Wang, Xiang; Zhang, Wen-Hao; Shi, Qian-Kun; Mu, Xin-Wei
Abstract : Objective: To investigate the association of plasma heparin-binding protein (HBP) with the development of acute gastrointestinal injury (AGI) in critically ill patients. Design: Clinical retrospective cross-sectional study. Setting: A general teaching hospital in China. Participants: Adult patients (age ≥18 years) admitted to our department with an intensive care unit (ICU) stay ≥5 days. Main outcome measures: HBP levels were recorded twice or more within 5 days after admission. The initial AGI grades and the worst AGI grades within 5 days after admission, the number of patients receiving total enteral nutrition (TEN) and the number of patients with feeding intolerance (FI) and with sepsis were also recorded, along with some clinical severity and outcome variables. Results: From June 2018 to May 2019, 221 patients were enrolled in this study. We divided patients into four groups based on the HBP values: HBP ≤20 ng/mL, 20<HBP ≤50 ng/mL, 50100 ng/mL. Significant differences were found in the ratios of AGI deterioration and TEN and the incidence rates of FI and sepsis among the four groups. Differences were also found among the groups regarding the worst AGI grades. The area under receiver operating characteristic curves for AGI deterioration, severe AGI (grades II or above), TEN and FI were 0.738 (p=0.001), 0.774 (p<0.001), 0.810 (p<0.001) and 0.729 (p=0.001), respectively. The optimal HBP cut-off values for AGI deterioration and severe AGI were 53.27 ng/mL and 41.26 ng/mL, respectively. However, no differences in ICU duration or 28-day mortality were found. Conclusions: HBP levels were associated with gastrointestinal dysfunction in critically ill patients. Increased HBP was positively correlated with sepsis but it was not correlated with 28-day mortality.